Quality of the Audit Committee, Company Size and Integrity of Financial Statements: Does Audit Quality an Important Role - Uli, Aprilla Sinta (Business Management, 2024)
The research aims to examine the Influence of audit committee quality, size of company and integrity of financial statement: How important quality of audit? Object of this research are secondary data is data that manufacturing company is a sample of 2015-2018 in the form of annual data in financial reporting that listed in BEI. That data are analyzed by multiple regression method and SPSS program version 21. The variables were examined are influence of audit committee quality, size of company and integrity of financial statement with quality of audit as moderating variable. The results of this research showed that audit committee quality and size of company have effect to integrity of financial statement with significance, quality of audit also empowering the influence of audit committee quality to integrity of financial statement significantly and size of company also have a strong effect to integrity of financial statement because of quality of audit variable. The results of this research also showed that the significance is under 0,05, which means the effect is well-strong. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study as market value, risk of reporting and level return.